2020
DOI: 10.1038/s41375-020-0791-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of nomogram-revised risk index and comparison with other models for extranodal nasal-type NK/T-cell lymphoma in the modern chemotherapy era: indication for prognostication and clinical decision-making

Abstract: Derived from our original nomogram study by using the risk variables from multivariable analyses in the derivation cohort of 1383 patients with extranodal NK/T-cell lymphoma, nasal-type (ENKTCL) who were mostly treated with anthracyclinebased chemotherapy, we propose an easily used nomogram-revised risk index (NRI), validated it and compared with Ann Arbor staging, the International Prognostic Index (IPI), Korean Prognostic Index (KPI), and prognostic index of natural killer lymphoma (PINK) for overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 41 publications
7
103
1
4
Order By: Relevance
“…Our results support previous observations that the baseline SUVmax correlates with prognosis in ENKTCL [35]. The PINK score represents a new model used to predict outcomes in ENKTCL patients treated with non-anthracycline-based therapies, and this model was con rmed in subsequent studies [7,36]. Our research assessed the impact of the PINK on prognosis and found that a high PINK score was associated with a worse outcome.…”
Section: Discussionsupporting
confidence: 89%
“…Our results support previous observations that the baseline SUVmax correlates with prognosis in ENKTCL [35]. The PINK score represents a new model used to predict outcomes in ENKTCL patients treated with non-anthracycline-based therapies, and this model was con rmed in subsequent studies [7,36]. Our research assessed the impact of the PINK on prognosis and found that a high PINK score was associated with a worse outcome.…”
Section: Discussionsupporting
confidence: 89%
“…In the ANT-based CT era, comparative studies do not show the survival benefit of adding CT to RT for early-stage ENKTCL 5,8,36,37 ; the advantage of additional CT has only been observed in high-risk early-stage patients. 10 Moving to the modern CT era, 33 the NRI here remained satisfactory for discriminating between low-risk and high-risk groups, and identified intermediate-risk to high-risk patients receiving substantial benefit from additional CT. Even with more effective CT, adding non-ANT-based CT to RT did not confer survival benefit for low-risk patients; survival benefit was still only observed in intermediate-risk/high-risk patients.…”
Section: Discussionmentioning
confidence: 97%
“…Patients were staged using the Ann Arbor staging system and stratified using the nomogram-revised risk index (NRI). 32,33 Verification and restaging based on original imaging reports were carried out during data cleaning process. Ann Arbor stage I was defined as primary extranodal lesion with or without adjacent invasion of the structure or organs, whereas stage II was defined as primary extranodal lesion with involvement of regional lymph nodes on the same side of the diaphragm.…”
Section: Evaluation Stage and Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nomograms are accurate and precise tools by creating an intuitive graph of a statistical predictive model for estimating risk, by correlating the relationship between parameters and various cancer prognosis parameters such as metastatic probability, overall survival (OS), and disease risk. 17,18 In our previous study, precancerous lesions (PL) of UGC screening are the major the detection result in non-high-incidence area. And to data, there has never been a study intended to develop a nomogram to predict the risk of UGPL.…”
Section: Introductionmentioning
confidence: 99%